2010
DOI: 10.1021/jp908174s
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Equilibrium of Formic Acid with Hydrogen and Carbon Dioxide Using Ionic Liquid

Abstract: The equilibrium for the reversible decomposition of formic acid into carbon dioxide and hydrogen is studied in the ionic liquid (IL) 1,3-dipropyl-2-methylimidazolium formate. The equilibrium is strongly favored to the formic acid side because of the strong solvation of formic acid in the IL through the strong Coulombic solute-solvent interactions. The comparison of the equilibrium constants in the IL and water has shown that the pressures required to transform hydrogen and carbon dioxide into formic acid can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 28 publications
0
57
0
1
Order By: Relevance
“…Indeed, Yasaka et al very recently investigated the equilibrium reaction of formic acid production from H 2 and CO 2 , with regard to using ILs as solvent. 220 They compared the equilibrium constants in [PPMIm][HCOO], water, and vacuum (to study the gas phase reaction), and they found that the Coulombic solvatation power present in the IL had a tremendously beneficial impact on the equilibrium toward the HCOOH side. The authors see in this method a possible future application for hydrogen storage, as formic acid can (unlike H 2 ) be easily stored and transported in the liquid state.…”
Section: Other Reactions Using Co 2 As Reactant In Combination With Imentioning
confidence: 99%
“…Indeed, Yasaka et al very recently investigated the equilibrium reaction of formic acid production from H 2 and CO 2 , with regard to using ILs as solvent. 220 They compared the equilibrium constants in [PPMIm][HCOO], water, and vacuum (to study the gas phase reaction), and they found that the Coulombic solvatation power present in the IL had a tremendously beneficial impact on the equilibrium toward the HCOOH side. The authors see in this method a possible future application for hydrogen storage, as formic acid can (unlike H 2 ) be easily stored and transported in the liquid state.…”
Section: Other Reactions Using Co 2 As Reactant In Combination With Imentioning
confidence: 99%
“…[4b,d] The resulting HCO 2 H/NHex 3 adduct can be separated and cleaved into free formic acid and amine by distillation. Yasaka et al proposed the use of imidazolium-based ILs with formate anions to stabilize HCO 2 H. [6] Herein we present a new concept that allows the continuous-flow hydrogenation of supercritical CO 2 (scCO 2 ) with integrated product separation from an immobilized catalyst and stabilizing base to produce pure HCO 2 H in a single processing unit. [5] After reaction, the solid catalyst is separated by filtration, and the formic acid can be distilled out from the basic IL.…”
mentioning
confidence: 99%
“…[9,[47][48][49][50][51][52] Formic acid contains only 4.4 wt% hydrogen, less than the previous mentioned materials. The abundance of carbon dioxide as substrate enhances the attraction of formic acid as simple and cheap hydrogen storage material.…”
Section: Formic Acidmentioning
confidence: 88%